S125 The effect of transcutaneous submental electrical stimulation on the blood pressure response in healthy volunteers. (11th November 2022) - Alsharifi, A; Carter, N; Akbar, I; Pascual, M; Cheng, M; Pengo, M; Parati, G; Kaltsakas, G; Rafferty, G; Steier, J
Abstract : Background: Transcutaneous electrical stimulation (TES) has been recently introduced to treat patients with sleep-disordered breathing (SDB). There are, however, few data on the effects of submental electrical stimulation on the cardiovascular system. We studied the effect of TES on the cardiovascular responses in healthy volunteers during head-down-tilt (HDT) induced baroreceptor loading. Method: Cardiorespiratory parameters were recorded for 5 mins while seated and supine, and during 10 mins HDT (50°) under normoxic, hypercapnic (FiCO2 5%) and poikilocapnic hypoxic (FiO2 12%) conditions. Blood pressure (BP) and was measured continuously using a Finapres device, and the average reported for the final 2 minutes of each condition. All participants were studied twice, once without and once with TES and gas conditions applied in random order. Submental TES (30Hz, pulse width 250 μs, bipolar current) was individually titrated to skin sensation. Data are presented as mean (SD), with a level of significance at p<0.05 and analysed using two-way ANOVA with Tukey's correction for multiple comparisons. The 95% confidence interval (CI) was reported for the difference (Δ) with TES. Results: We studied 13 healthy subjects (age 29 (12) years, 6 female, BMI 23 (1.6) kg/m 2 ). With TES (current 8(2) mA), diastolic BP decreased significantly during hypoxia when supine (Δ-17.8 (13.6) mmHg, ( 95 % CI, -30.5 to -5.1), p=0.005) and during HDT (Δ-22.0 (15.7) mmHg, ( 95 % CI, -36.7 to -7.3), p=0.003). Systolic BP also decreased with hypoxia when HDT (Δ-21.0 (20.0) mmHg, ( 95 % CI, -39.6 to -2.3), p=0.025). Mean arterial BP decreased during hypoxia when supine (Δ-19.1 (15.8) mmHg, ( 95 % CI, -33.9 to -4.4), p=0.009) and during HDT (Δ-20.6 (15.5) mmHg, ( 95 % CI, -35.0 to -6.1), p=0.005). There was no associated change in the heart rate with TES (p=ns), but a trend towards increased minute ventilation when seated and breathing room air (p=0.060). Conclusion: Submental electrical stimulation appears to sensitise baro- and chemoreceptor function, leading to substantially reduced blood pressure while exposed to hypoxic conditions in supine posture in healthy subject. These findings have implications for the cardiorespiratory control of patients with hypertension and those with sleep-disordered breathing.